2004
DOI: 10.1136/hrt.2003.014753
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the expression of haemorheological determinants in individuals with atherothrombotic risk factors and in apparently healthy people

Abstract: Background: Increased red cell aggregation can be detrimental, leading to slow capillary blood flow and tissue hypoxaemia. Sex differences in the degree of erythrocyte adhesiveness/aggregation in the peripheral blood have not been clearly shown. Objectives: To determine whether there are sex differences in the expression of erythrocyte adhesiveness/ aggregation in the peripheral blood in individuals with atherothrombotic risk factors and in apparently healthy people. Methods: From a cohort of 965 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
3
18
1
1
Order By: Relevance
“…Second, we did not account for time spent outdoors, which depends on the work status and occupation type of each individual in the study. Third, as gender has been known to have a significant role in inflammation (Zeltser et al, 2004) and air pollution research (Chen et al, 2005) this might have stumped our results. Finally, we note that most previous studies have shown a significant decrease in combustion derived air pollutants in distances of above 400 meters (Brugge et al, 2007).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Second, we did not account for time spent outdoors, which depends on the work status and occupation type of each individual in the study. Third, as gender has been known to have a significant role in inflammation (Zeltser et al, 2004) and air pollution research (Chen et al, 2005) this might have stumped our results. Finally, we note that most previous studies have shown a significant decrease in combustion derived air pollutants in distances of above 400 meters (Brugge et al, 2007).…”
Section: Discussioncontrasting
confidence: 44%
“…Among the possible reasons for the previous conflicting results, in similar studies are: the lack of consistent air pollution measurement methodology, the lack of systematic examination of the time relationship between air pollution variables and markers of inflammation, and the fact that not all studies were controlled for multiple possible confounders. These confounders include parameters with known influences on the inflammatory response such as age (Larbi et al, 2004), gender (Zeltser et al, 2004), body mass index (BMI) and waist circumference (Santos et al, 2005), exercise (Petersen & Pedersen, 2005), the presence of hyperlipidemia (Pirro et al, 2004), hypertension (Tsioufis et al, 2006), alcohol consumption (Imhof et al, 2001), smoking habits (Yasue et al, 2006), glucose concentrations (Kerner et al, 2005), as well as the intake of medications with a potential pro-and anti-inflammatory effect (Kushner et al, 2006). In addition there are many possible confounders regarding air pollution, mainly meteorological parameters (temperature, humidity and precipitants) which may also be related to cardiovascular events (Danet et al, 1999) as well as wind speed (Brugge et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we analyzed the data collected during the last 5 years in the Tel Aviv Medical Center Inflammation Survey, a registered data bank of the Israeli Ministry of Justice [5][6][7][8][9][10][11]. This is a relatively large survey composed of apparently healthy individuals attending a center for periodic health examinations.…”
Section: Study Populationmentioning
confidence: 98%
“…We have presently analyzed data that have been collected during the last 5 years at the Tel Aviv Medical Center Inflammation Survey, a registered data bank of the Israeli Ministry of Justice [9][10][11][12][13][14]. This is a relatively large cohort of individuals who attended our medical center for a routine annual checkup and gave their written informed consent for participation according to the instruction of the local ethics committee.…”
Section: Subjectsmentioning
confidence: 99%